2015
DOI: 10.4238/2015.september.22.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dehydroepiandrosterone treatment on hormone levels and antioxidant parameters in aged rats

Abstract: ABSTRACT. The aim of the current study was to evaluate the effect of chronic dehydroepiandrosterone (DHEA) administration on steroid hormones and antioxidant parameters in aged rats. To this end, three groups of Sprague-Dawley rats were compared: young (3 months of age) untreated; aged (19 months old) untreated; and aged rats treated with 20 mg/kg DHEA for 8 weeks. Major organs of aged rats in the untreated group demonstrated physiological atrophy, compared to those of young rats; this effect appeared to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Dehydroepiandrosterone (DHEA) and the more abundant dehydroepiandrosterone sulfate (DHEAS) are important precursors of the active sex hormones testosterone and estradiol. DHEA has been hypothesized to reverse vascular remodeling, improve vascular endothelial cell function, and reduce oxidative stress (7)(8)(9). Previous studies have shown that, in men, low serum levels of DHEA increase the risk of CHD; however, the relationship between DHEAS and CHD is contradictory (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Dehydroepiandrosterone (DHEA) and the more abundant dehydroepiandrosterone sulfate (DHEAS) are important precursors of the active sex hormones testosterone and estradiol. DHEA has been hypothesized to reverse vascular remodeling, improve vascular endothelial cell function, and reduce oxidative stress (7)(8)(9). Previous studies have shown that, in men, low serum levels of DHEA increase the risk of CHD; however, the relationship between DHEAS and CHD is contradictory (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The body weight gain of perimenopausal rats was significantly more than that noted in young adult rats. However, Yin et al (2015) reported that the change in body weight between the young and old rats is insignificant. On the other hand, DHEA-treated perimenopausal rats gained less body weight than observed in non-treated perimenopausal rats.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, DHEA levels present a negative correlation with the NOR index, suggesting a negative action on diabetic encephalopathy. This is quite surprising, since the protective and antioxidant actions of this steroid are well known [ 77 ], even if its actions have been better described during aging [ 78 , 79 ]. Moreover, in this paper, we reported increased hippocampal levels of PREG and PROG that, as stated above, show a similar pattern in plasma.…”
Section: Discussionmentioning
confidence: 99%